An adamantane-based COF: stability, adsorption capability, and behaviour as a catalyst and support for Pd and Au for the hydrogenation of nitrostyrene. Issue 23 (7th November 2016) - Trandafir, M. M.; Pop, L.; Hădade, N. D.; Florea, M.; Neațu, F.; Teodorescu, C. M.; Duraki, B.; van Bokhoven, J. A.; Grosu, I.; Pârvulescu, Vasile I.; Garcia, Hermenegildo
Abstract : A bimodal (micro/mesoporous) COF was synthesized by coupling tetrakis-1, 3, 5, 7-(4′-iodophenyl)adamantane with 4, 4′-diethynylbiphenyl following a Sonogashira protocol. Abstract : A bimodal (micro/mesoporous) COF was synthesized by coupling tetrakis-1, 3, 5, 7-(4′-iodophenyl)adamantane with 4, 4′-diethynylbiphenyl following a Sonogashira protocol. The COF preparation strategy led, however, to the incomplete recovery of the palladium catalyst and ICP-OES analysis indicated that around 0.1 wt% palladium remained inside the pores. Noteworthily, the remnant palladium catalyst is still accessible and can be valorised in additional catalytic reactions like the hydrogenation of nitrostyrene. Further deposition of 0.5 wt% active metals (like palladium or gold) enhanced the catalytic activity and tuned the catalyst selectivity with respect to analogous metal catalysts prepared using active carbon as a support. The resulting COF-supported metal NPs are stable and recyclable catalysts. Under normal conditions, this COF is also able to adsorb large amounts of weak electrophilic gases like carbon dioxide.